PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS PENDEKATAN KONTEKSTUAL PADA MATERI POLA BILANGAN KELAS VIII SMP - Tia Fitri Amanda (Jurnal Edukasi dan Penelitian Matematika, 2022)
This research was conducted at SMPN 1 X Koto Singkarak which aims to develop a valid and practical learning videos based on a contextual teaching learning approach on number pattern used as a learning media to attract student’s attention and help their learning process to be more active. The development of these video uses Plomp Model which has three stages, namely Preliminary research, prototyping phase and assessment phase. Formative evaluation is carried out on learning videos that are developed to become better products.  From the result of the development of this learning video obtained a validity value 85.10 % with a very valid category, the value of practicality based on student’s resposes in 86.45 % with a very practical category and the value of practicality based on teacher’s respond in 81,25% with practical category. Base on this, the learning video based on the contextual teaching learning approach that has been developed is valid and practical. Keywords — Learning Media, Learning Video, Contextual Teaching Learning Approach